Aging of UV curable PDMS developed for large-scale, high viscosity stereolithography. (January 2023) - Song, Hongtao; Rodriguez, Nicholas A.; Oakdale, James S.; Duoss, Eric B.; Crawford, Richard H.; Seepersad, Carolyn C.
Highlights: The aging behavior of a novel Pt-catalyzed, UV-curable PDMS formulation developed for stereolithography is investigated under thermal and UV accelerated aging conditions. The Pt-catalyzed, UV-curable PDMS formulation is 'under-cured' after being printed and slowly evolves over time resulting in increased stiffness and decreased elongation, likely due to the formation of additional crosslinks. FTIR spectroscopy indicates that no new chemical bonds or functional groups are generated through the aging process, suggesting that no thermal degradation or polymer chain scissions occur in the polymer matrix. Overall, this novel PDMS formulation exhibits greater mechanical strength and significantly less reduction in strength with aging, compared with the commonly used, UV-curable thiol-ene PDMS, making it an excellent candidate for photopolymerization applications in additive manufacturing Abstract: Polydimethylsiloxane (PDMS) elastomers are silicone rubbers that find widespread application in both academic and industrial settings. This study investigates the use of photosensitive platinum catalysts for UV-activated hydrosilylation of PDMS, which enables the additive manufacturing of PDMS objects through techniques such as stereolithography. Specifically, this study focuses on understanding the aging behavior of Pt-catalyzed, UV-curable PDMS samples, including their mechanical behavior under thermal and UV-accelerated aging conditions. The results show that the Pt-catalyzed, UV-curable PDMS introduced in this research is 'under-cured' after being printed and will slowly evolve over time resulting in increased stiffness and decreased elongation, likely due to the formation of additional crosslinks. FTIR spectroscopy indicates that no new chemical bonds or functional groups are generated through the aging process, suggesting that no thermal degradation or polymer chain scissions occur in the polymer matrix. Overall, this PDMS formulation exhibits greater mechanical strength and significantly less reduction in strength with aging, compared with the commonly used, UV-curable thiol-ene PDMS.